Expression of the extracellular matrix component brevican prior and after deep brain stimulation in the dtsz hamster model of dystonia - Anika Lüttig; Stefanie Perl; Denise Franz; Malin Kotyra; Markus Morawski; Rüdiger Köhling; Angelika Richter (Brain Research Bulletin, 2025)
Maladaptive plasticity is thought to be involved in dystonia and paroxysmal dyskinesia, which often occur in early life in children and in animals. While the pathophysiology of these disorders is poorly understood, canine paroxysmal dyskinesia can be caused by a deletion in the gene, encoding the brain-specific component of the extracellular matrix (ECM) brevican (Brev). Brev plays a crucial role in the maturation of parvalbumin-reactive GABAergic interneurons (PV+). Therefore, in the present study we investigated whether abnormal expression of Brev coincides with age-dependent dystonia in the dtsz hamster, a model of paroxysmal dystonia in which previous studies indicated altered maturation of striatal PV+. In addition, we examined if changes in Brev expression might be involved in antidystonic effects of deep brain stimulations (DBS) of the entopeduncular nucleus (EPN; analogue of the globus pallidus internus in primates). In comparison to age-matched non-dystonic control hamsters, dtsz mutant hamsters showed a higher Brev expression in the ventral thalamic nucleus (21 and 35 days) and a lower number of Brev+ cells in the motor cortex (35 days). Furthermore, there were age-dependent differences especially a lower number of Brev+ cells in the motor cortex and a higher single cell intensity in the EPN (each in comparison to 21 and 90 days) at the age of 35 days (the age of maximum severity of dystonia). Brevican intensity seems to decrease at the age of 90 days (the age of spontaneous remission of dystonia) in some brain regions. EPN-DBS for 3 h was probably too short to induce significant changes as an explanation for recent electrophysiological data on cortico-striatal responses after DBS, but in sham-stimulated animal groups, the genotype-differences in motor cortex and thalamus could be confirmed. The present findings suggest that ECM warrant consideration in dystonia research.